Respiration of the Black Sea Turbot (Scophthalmus maeoticus) Eggs as an Indicator of its Development - Antonina N. Khanaychenko (Журнал Сибирского федерального университета: Серия Биология, 2017)
Rate of oxygen consumption of the Black Sea turbot (Scophthalmus maeoticus) during early ontogenesis depending on stage of development, morphological norm and temperature (11 and 16 °C) was studied. Oxygen consumption at blastula stage was the lowest, varied between 0.0057 and 0.0061 mg O2 ind-1 h-1 and was independent among egg batches in studied temperature range. Aerobic metabolism increased 22 times at 16 °C, reaching 0.1348±0.0205 mg O2 ind-1 h-1, and only 13 times at 11 °C from blastula to active embryo stage. Temperature interval 5 °С gave a mean Q10 of 2.6 for the rate of oxygen consumption of the Black Sea turbot during embryogenesis. Aerobic metabolism appeared twice lower at gastrula stage in embryos with morphological defects revealed from tail bud stage onwards incompatible with the development to a viable larvae, than that in normally developing embryos